The Impact of Human Cpaital on the Internationalisation of Technology SMEs - Nickerson, Christian (2014)
As the world has continued to globalise, the importance of internationalisation theory has grown. Most of the focus for internationalisation theory has traditionally centred on MNE international expansion. However, a new field of International Entrepreneurship has opened up to help explain the recent, yet significant international expansion of SMEs. The aim of this paper is to add to this field of theory. To do this paper will analyse the skills that affect Technology SMEs ability to internationalise. The paper presents four different case studies to show case the different effects different skills have on internationalisation. Finally the paper attempts to integrate these findings into international entrepreneurship, whilst carving its own niche the in the academic landscape as a result of the significance of these findings.